Spin-state control of cobalt(ii) and iron(ii) complexes with click-derived tripodal ligands through non-covalent and fluorine-specific interactions. Issue 48 (1st December 2021) - Nößler, Maite; Hunger, David; Reichert, Felix; Winkler, Mario; Reimann, Marc; Klein, Johannes; Suhr, Simon; Suntrup, Lisa; Beerhues, Julia; Kaupp, Martin; van Slageren, Joris; Sarkar, Biprajit
Abstract : Fluorine-specific interactions in the secondary coordination sphere of iron(ii ) and cobalt(ii ) complexes with click-derived fluorinated tripodal ligands are shown to control the spin states of the metal centers. Abstract : The fine-tuning of intermolecular or intramolecular non-covalent interactions (NCIs) and thus the precise synthesis of metal complexes in which the spin states can be controlled by NCIs remains challenging, even though several such complexes have been intensively studied. In this regard, we present mononuclear cobalt(ii ) and iron(ii ) complexes with "click"-derived tripodal ligands that contain fluorinated benzyl substituents in the secondary coordination sphere. The complexes were co-crystallized with different solvent molecules to decipher the effect of the crystallized solvents on NCIs, and on the spin state of the metal ion. Additionally, the fluorine-specific interactions in the secondary coordination sphere were examined. We present a first structure-property correlation between the nature of interaction of the (per)fluorinated aromatic substituents on the ligand periphery, and the spin state of the metal complexes. In particular, the TF5 TA containing ligand show interesting stacking motifs depending on the used solvent, and these interactions have an influence on the spin state of the cobalt(ii ) complexes. Furthermore, the iron(ii ) complex thereof, Fe(TF5 TA)2 (BF4 )2 ·2EtOH displays spin crossover (SCO).